Philippines : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Philippines. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that the Philippine economy has continued to perform strongly. Real GDP regained strength from a slowdown in mid-2015 to record a robust 5.9 percent growth rate in 2015 and 6.9 percent in the first half of 2016. Both consumption and investment grew rapidly, while net exports were held back by weak external demand. Job creation was also strong: the unemployment rate declined to 6.3 percent in 2015 and 6.0 percent in the first half of 2016. The outlook for the Philippine economy remains favorable despite external headwinds. Real GDP growth is expected at 6.4 percent in 2016 and 6.7 percent in 2017 on continued robust domestic demand and a modest recovery in exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet